Diagnosis of Hirschsprung's disease by punch biopsy of rectum. - Pease, P W (1976)
234 punch biopsy specimens of rectal tissue were taken from 112 children. In 94% of the patients the diagnosis of Hirschsprung's disease was confirmed or refuted by the first biopsy. There were no false-positive or false-negative results. One patient developed a serious complication, a pelvic haematoma.